2021
DOI: 10.1007/s12020-021-02890-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based clinical outcome prediction in surgery for acromegaly

Abstract: Purpose Biochemical remission (BR), gross total resection (GTR), and intraoperative cerebrospinal fluid (CSF) leaks are important metrics in transsphenoidal surgery for acromegaly, and prediction of their likelihood using machine learning would be clinically advantageous. We aim to develop and externally validate clinical prediction models for outcomes after transsphenoidal surgery for acromegaly. Methods Using data from two registries, we develop and exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The most common population studied were general samples of patients with PAs, without distinction (8 studies) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Acromegaly patients were the main population in five studies [ 18 , 35 , 36 , 37 , 38 ]. Furthermore, Cushing disease (CD) patients were the focus in four additional studies [ 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most common population studied were general samples of patients with PAs, without distinction (8 studies) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Acromegaly patients were the main population in five studies [ 18 , 35 , 36 , 37 , 38 ]. Furthermore, Cushing disease (CD) patients were the focus in four additional studies [ 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Cushing disease (CD) patients were the focus in four additional studies [ 39 , 40 , 41 , 42 ]. Only two studies reported a multicenter setting for external validation [ 18 , 38 ]. Only Qiao et al reported the use of a prospective sample for internal validation [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations